(3eQhL GdPgH heYGOf GdLhgQs - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO heSJhLH GdKfGA s
(3BNQgG (B:s
(3JfJgi HCNHGQ eYGhjI Hf CHj SajGf s
(3GfXQ Qbe (B472 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B80s
Keywords: (3GdJGQjNs